Needs Assessment in Training Courses for Caregivers on Dependent Elderly Care - Thummakul, Doungnetre; Kwanyuen, Renu; Chusri, Orranuch; Jaingam, Natrapee (Princess of Naradhiwas University Journal, 2023)
The objective of the research was to study the needs for training courses for caregivers on dependent elderly. The sample group was 66 village health volunteers from Ban Long Tong subdistrict, Song Phi Nong district, Suphanburi province. Data were collected from April 2022 to May 2022. The tool included a needs assessment survey which was verified by 3 experts, and received the Index of Consistency at 0.67-1.00, and Cronbach’s alpha at 0.89. Data were analyzed by statistics including percentage, mean, standard deviation and modified priority needs index (PNI modified). The results showed that needs for the training courses, from authentic assessment, were at a moderate level (M=3.55, S.D.= 0.50). The provision for needs assessment in training was at the highest level (M=4.71, S.D. = 0.45). The results showed that the training topics ranging from the most needed to the least were as follows: 1) Stress care 2) Technology in personal care and in senior care 3) Health promotion; food and nutrition for seniors 4) The rights of senior citizens; Labor law 5) Dependent elderly care 6) First aid for elderly care 7) Drugs prescribed to elderly people 8) Crisis and first aid 9) Care for elderly people who are unable to help themselves due to age, gastrointestinal tract disease, respiratory, excretory, and genital diseases and 10) Roles and ethics of elderly caregivers (PNI modified=0.348, 0.346, 0.342, 0.336, 0.331, 0.329, 0.326, 0.315, 0.300, and 0.290, respectively). The findings from the study can be used as a guideline for development of training courses for dependent elderly care.